2020
DOI: 10.1111/aec.12994
|View full text |Cite
|
Sign up to set email alerts
|

The effects of natural and artificial edges on phenology: A case study of Ctenitis submarginalis

Abstract: Habitat fragmentation increases forest edges, which in turn influence the microclimate to which ferns are exposed. Ferns do not depend on pollinators or dispersers, which make abiotic variables responsible for triggering the manifestation of their phenophases. Phenology has been an important tool in understanding the effects of habitat fragmentation on plant behaviour. Our aims were to compare the phenology of populations of the fern Ctenitis submarginalis at a natural edge, an artificial edge and in the fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…When the mean temperature reaches 20 °C, there is an intensification of senescence and leaf renewal decline reducing the second leaf renewal event by 10%. It is already registered that the increase in temperature also causes a reduction in the rates of leaf renewal and fertility in fern species growing in southern Brazil (Müller & Schmitt 2019;Müller et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When the mean temperature reaches 20 °C, there is an intensification of senescence and leaf renewal decline reducing the second leaf renewal event by 10%. It is already registered that the increase in temperature also causes a reduction in the rates of leaf renewal and fertility in fern species growing in southern Brazil (Müller & Schmitt 2019;Müller et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, natural forests (NFs) have a higher species richness than planted forests (PFs), and consist of more complex and stable communities with diverse age structures (You et al., 2023). Consequently, the phenologies of natural and planted forests may differ due to varying stresses from human interventions (Müller et al., 2021; Nunes et al., 2022). For example, a previous study found that understory herbs in intensively managed forests flower later in spring, suggesting potential far‐reaching consequences for the ecology and evolution of the understory communities (Willems et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral microclimatic conditions differ from those in the interior of remaining forests, mainly due to decreased humidity and increased luminosity, temperature, and wind incidence (Murcia, 1995;Silva, Mehltreter & Schmitt, 2018). The use of surrounding land affects the intensity of microclimatic stresses at forest edges, with a direct connection between the type of use and the response of forest remnants to edge effects (Laurance et al, 2007;Müller et al, 2020). Understanding these responses is fundamental to the implementation of effective forest management actions according to distinct situations and edge effect patterns (Hardt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%